Pengaruh Model Pembelajaran Group Investigasi Berbantuan Media Flashcard Terhadap Minat Dan Hasil Belajar - Febriyanti, Dinda Fitri; Ismatulloh, Kholida (Universitas Hamzanwadi, 2019)
This study aims to determinan the influence of the learning model group investigation combined with flashcard media on student interest and learning outcomes in the subject of multimedia x graphic class design in SMK Negeri 1 praya. This type of research is quantitative whit Pre-Experimental Design methos. The population of this study was all students of class x multimedia SMK Negeri 1 Praya totaling 30 student, with samples using the saturation sampling technique (sensus). Multimedia class x as an ekperimental class with 30 a total dtudents. Research design used of One-Group Pretest Posttest. Data collection userd questionnaires and learning tests. Data analysis techniques using Paired Sample T Test. The results showed that 1) there was an influence of the learning group investigation model combined with the flashcard media on students interest in learning (with a significance value of p < 0,05) (0,000<0,05). 2) there was an influence of the learning group investigation model combined with the flashcard media on students in learning outcomes (with a significance value of p < 0,05) (0,000<0,05). Thus it was concluded that there was an influence of the cooperative learning type group investigation model combined with the flashcard learning media students interest and student learning outcomes in the basic subjects of graphic x grade multimedia design at SMK Negeri 1 Praya shcool year 2019/2020.